1968
DOI: 10.1017/s0022172400028394
|View full text |Cite
|
Sign up to set email alerts
|

Acute glomerulonephritis in Trinidad: serological typing of group A streptococci

Abstract: The recent epidemic of acute glomerulonephritis in Trinidad had two peaks, separated by an interval of about 6 months.Evidence is presented that there were in fact two successive but overlapping epidemics, the first due to streptococci of provisional M-type 55, and the second to streptococci of M-type 49.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

1970
1970
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 19 publications
1
17
1
Order By: Relevance
“…They appear to be of moderate virulence and non-nephritogenic, and to have little if any affinity for respiratory tissues. While Parker found that in a series of patients there tended to be a sequence of streptococcal types during the course of their illness (Parker et al 1968), our cases were remarkable for the purity and consistency of their culture isolates during an episode of infection. A further unusual feature is the long-term presence of the two strains in almost unchanged proportions in the affected population.…”
Section: Discussionmentioning
confidence: 53%
“…They appear to be of moderate virulence and non-nephritogenic, and to have little if any affinity for respiratory tissues. While Parker found that in a series of patients there tended to be a sequence of streptococcal types during the course of their illness (Parker et al 1968), our cases were remarkable for the purity and consistency of their culture isolates during an episode of infection. A further unusual feature is the long-term presence of the two strains in almost unchanged proportions in the affected population.…”
Section: Discussionmentioning
confidence: 53%
“…Neither M-type 57 strains nor antibodies (with one exception) were found before that time, while both were present subsequently. This type also nearly disappeared as T-type 4 The highest titers of type-specific antibody were obtained in the tests for M-type 55 antibody in 1965. Several BI's were well over 100.…”
Section: Resultsmentioning
confidence: 88%
“…M-type 49 strains also have been identified in our laboratory from two boys who had acquired skin lesions in Puerto Rico and developed nephritis following their return to Chicago, from skin lesions on a child with nephritis in the Panama Canal Zone, and from the sibling of a young patient with acute nephritis in Chicago. Identification of this type in 38% of the strains from nephritic patients in Trinidad, compared with 15% of the strains from school children (4) indicates its importance in the second wave of the 1965 epidemic. Failure to find M-type 49 antibodies in more than 17% of patients ill at that time may have resulted from factors affecting antibody response (vide infra) rather than to absence of infection with this streptococcal type.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…' Other groups of streptococci were not commonly isolated from lesions: Group G in four instances, Groups B and C in none. (2,3,9,19,20). In Fig.…”
Section: Methodsmentioning
confidence: 99%